Kyanmabase, « Bonne santé à vous ! ». Logiques et pratiques d’automédication en Arakan (Birmanie) - Céline Coderey (Anthropologie & Santé)
Based on fieldwork conducted in the Thandwe area of Arakan (Burma), this article explores pharmaceutical pluralism and the important role it plays in people’s health-seeking process, especially through the practice of self-medication. People choose among the different products available and often use self-medication instead of consulting a specialist. The aim of the paper is to show how this largely stems from the individuals’ conceptions about the composition and the “biography” of the products, as well as from the political, social and economic contexts in which they live.